2019
DOI: 10.3389/fpsyg.2019.00972
|View full text |Cite
|
Sign up to set email alerts
|

Type of Delivery, Neuropsychological Development and Intelligence in Twin Births

Abstract: Based on a retrospective cohort design with 6-year-old children born in twin births, the relationship between verbal, non-verbal, global neuropsychological development, general intelligence and type of delivery has been studied. To this end, the possible effect of third gestational, obstetric and neonatal variables, such as maternal age at delivery, fetal presentation, gestational age, newborn weight and Apgar at minute one, was controlled. The exposed cohort includes children born by cesarean section, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 62 publications
(100 reference statements)
4
25
0
4
Order By: Relevance
“…The observed results were not affected by any of the tested confounders. These outcomes correspond to those from studies by Polidano et al [ 7 ], Curran et al [ 10 ], and Gonzales-Valenzuela et al [ 11 ]. Potential effects of the type of delivery on cognitive development in children should also be followed in our cohorts in the future to see if the observed changes are long-lasting or if they disappear at a later age.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The observed results were not affected by any of the tested confounders. These outcomes correspond to those from studies by Polidano et al [ 7 ], Curran et al [ 10 ], and Gonzales-Valenzuela et al [ 11 ]. Potential effects of the type of delivery on cognitive development in children should also be followed in our cohorts in the future to see if the observed changes are long-lasting or if they disappear at a later age.…”
Section: Discussionsupporting
confidence: 89%
“…The impact of the two different modes of delivery on neuropsychological development was also investigated by Gonzales-Valenzuela et al [ 11 ] who compared vaginal ( n = 84) and cesarean delivery ( n = 40) in 6 year old children born in twin births. Children were evaluated in their first year of primary school, using the Child Neuropsychological Maturity Questionnaire and Kaufman’s Intelligence Test.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in multiple deliveries requiring a caesarean section, there are some circumstances interfering in children's neurological development that could explain, at least partially, the long‐term cognitive and linguistic difficulties typically found in children with LDs in reading, writing, and arithmetic. In recent studies, type of birth has been found to be associated as an independent risk factor with neuropsychological development disorders and intellectual difficulties (González‐Mesa et al, ; González‐Valenzuela et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although some studies have reported a greater risk of mortality in the second twin following vaginal delivery when compared to the co‐twin (Armson et al, ; Wen et al, , ; Yang et al, ) other studies have been unable to demonstrate any benefits of elective caesarean in relation to vaginal delivery of the second twin (Greig, Veille, Morgan, & Henderson, ; Guerra et al, ; Hogle, Hutton, McBrien, Barret, & Hanna, ; Rabinovici, Barkai, Reichman, Serr, & Mashiach, ). Furthermore, the risks of caesarean delivery versus spontaneous vaginal delivery include low Apgar scores, neonatal respiratory morbidity, perinatal mortality due to uterine rupture or placenta praevia, and placental abruption in subsequent pregnancies (González‐Valenzuela, González‐Mesa, Cazorla‐Granados, & López‐Montiel, ; Hogle et al, ; Pasupathy & Smith, ; Villar et al, ; Wallin, Ekström, Marsal, & Källén, ). However, some studies seem to show that caesarean sections reduce the risk of low 5‐min Apgar scores and intrapartum fetal death of the first twin with breech presentation at labor, but they increase the risk of maternal and neonatal mortality and morbidity in cases of cephalic presentation (Hogle et al, ; Villar et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation